A high-strength aluminum alloy core aluminum stranded wire for overhead conductors and a manufacturing method thereof
By optimizing the structure and manufacturing process of aluminum alloy core aluminum stranded wires, combining high-strength and high-conductivity aluminum-magnesium silicon alloy wires and hard aluminum alloy wires, the problem of difficult to take into account the conductivity and strength of existing all-aluminum alloy stranded wires is solved, achieving more efficient transmission performance and lower production costs.
Patent Information
- Application Number
- CN202410025735.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-08
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-01-08
AI Technical Summary
The existing all-aluminum alloy stranded wires are difficult to take into account both conductivity and strength, resulting in the problem of high conductivity and low strength or high strength, which seriously restricts its application.
By optimizing the structure and manufacturing process of aluminum alloy core aluminum stranded wires, aluminium magnesium silicon alloy wires with tensile strength greater than 340MPa and hard aluminum alloy wires with conductivity greater than 63% IACS are used, combined with scientific stranded wire structure design and efficient manufacturing process, the strength and conductivity of aluminum alloy core aluminum stranded wires are improved.
It achieves lower resistance and higher conductivity of aluminum alloy core aluminum stranded wire under the same cross-sectional area, reduces the power loss of the line, improves transmission efficiency and power utilization efficiency, and reduces production costs.
Smart Images

Figure CN117976311B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aluminum alloy conductor manufacturing, and in particular relates to a high-strength aluminum alloy core aluminum stranded wire for overhead conductors and a manufacturing method thereof. Background Art
[0002] Overhead aluminum stranded wire is a carrier for long-distance power transmission, and its performance directly determines the power transmission capacity and power loss of the line. Ordinary steel core aluminum stranded wire has high resistivity and poor conductivity, resulting in small line transmission capacity and large power loss, causing huge waste of power resources. In addition, ordinary steel core aluminum stranded wire also has problems such as heavy weight, poor sag characteristics, poor corrosion resistance, short life cycle, high construction and maintenance costs, etc., which can no longer adapt to the development of the economy and society.
[0003] In order to reduce the power loss of transmission lines and improve the transmission efficiency and power utilization efficiency, the State Grid has vigorously advocated scientific and technological innovation in recent years, improved the technical level of power grid construction, and strengthened the application of all-aluminum alloy stranded wires. However, due to the mutual restriction between the conductivity and strength of aluminum alloys, it is difficult to balance the improvement of conductivity and strength. The existing all-aluminum alloy stranded wires still generally have the problem of high strength and low conductivity or high conductivity and low strength, which seriously restricts the application of all-aluminum alloy stranded wires. Therefore, the existing all-aluminum alloy stranded wires and their manufacturing methods still need to be improved and developed. Summary of the invention
[0004] The purpose of the present invention is to provide a high-strength aluminum alloy core aluminum stranded wire for overhead lines and a manufacturing method thereof in view of the above-mentioned problems and shortcomings, and to improve the strength and conductivity of the aluminum alloy core aluminum stranded wire by optimizing the structure and manufacturing process of the aluminum alloy core aluminum stranded wire, thereby reducing the line power loss of long-distance power transmission and improving the power transmission efficiency.
[0005] The technical solution of the present invention is achieved in this way:
[0006] The first aspect of the present invention provides a high-strength aluminum alloy core aluminum stranded wire for overhead conductors, which is characterized in that, in order from the center to the outside, a central aluminum-magnesium-silicon alloy wire, an aluminum-magnesium-silicon alloy wire inner layer, an aluminum-magnesium-silicon alloy wire middle layer, an aluminum-magnesium-silicon alloy wire outer layer, a hard aluminum alloy wire inner layer, a hard aluminum alloy wire middle layer and a hard aluminum alloy wire outer layer are sequentially arranged, the aluminum-magnesium-silicon alloy wire inner layer, the aluminum-magnesium-silicon alloy wire middle layer and the aluminum-magnesium-silicon alloy wire outer layer are respectively composed of a plurality of aluminum-magnesium-silicon alloy wires, the hard aluminum alloy wire inner layer, the hard aluminum alloy wire middle layer and the hard aluminum alloy wire outer layer are respectively composed of a plurality of hard aluminum alloy wires, the aluminum-magnesium-silicon alloy wire inner layer is spirally wound around the central aluminum-magnesium-silicon alloy wire, and the aluminum-magnesium-silicon alloy wire inner layer is spirally wound around the central aluminum-magnesium-silicon alloy wire. Gold wire, the middle layer of the aluminum-magnesium-silicon alloy wire is spirally wound on the inner layer of the aluminum-magnesium-silicon alloy wire in a direction opposite to the winding direction of the inner layer of the aluminum-magnesium-silicon alloy wire, the outer layer of the aluminum-magnesium-silicon alloy wire is spirally wound on the middle layer of the aluminum-magnesium-silicon alloy wire in a direction opposite to the winding direction of the middle layer of the aluminum-magnesium-silicon alloy wire, the inner layer of the hard aluminum alloy wire is spirally wound on the outer layer of the aluminum-magnesium-silicon alloy wire in a direction opposite to the winding direction of the outer layer of the aluminum-magnesium-silicon alloy wire, the middle layer of the hard aluminum alloy wire is spirally wound on the inner layer of the hard aluminum alloy wire in a direction opposite to the winding direction of the inner layer of the hard aluminum alloy wire, and the outer layer of the hard aluminum alloy wire is spirally wound on the middle layer of the hard aluminum alloy wire in a direction opposite to the winding direction of the middle layer of the hard aluminum alloy wire.
[0007] Preferably, the diameter of the aluminum-magnesium-silicon alloy wire is 2-3.5 mm, the tensile strength of the aluminum-magnesium-silicon alloy wire is ≥340.4 MPa, the yield strength is ≥320.9 MPa, the elongation after fracture is ≥5.4%, and the DC resistivity at 20°C is ≤0.0307Ω·mm 2 / m, electrical conductivity ≥56.1%IACS.
[0008] Preferably, the diameter of the hard aluminum alloy wire is 3.5-5 mm, the tensile strength of the hard aluminum alloy wire is ≥200.9 MPa, the yield strength is ≥181.5 MPa, the elongation after fracture is ≥8.1%, and the DC resistivity at 20°C is ≤0.0272Ω·mm 2 / m, electrical conductivity ≥63.5%IACS.
[0009] Preferably, the aluminum-magnesium-silicon alloy wire is composed of the following components in mass percentage: Mg 1.1-1.15%, Si 0.88-0.92%, and the balance is Al and unavoidable impurities, with a single impurity ≤0.05% and a total impurity content ≤0.1%.
[0010] Preferably, the hard aluminum alloy wire is composed of the following components in mass percentage: Fe 0.23-0.27%, the balance being Al and unavoidable impurities, with a single impurity ≤0.05% and a total impurity content ≤0.1%.
[0011] A second aspect of the present invention provides a method for manufacturing a high-strength aluminum alloy core aluminum stranded wire for an overhead conductor, which is characterized by comprising the following steps in sequence:
[0012] Step 1: melting and preparing aluminum-magnesium-silicon alloy liquid and hard aluminum alloy liquid at 700-720° C. according to the components and mass percentage of aluminum-magnesium-silicon alloy wire and hard aluminum alloy wire;
[0013] Step 2: Use argon gas with a purity of 99.99% and a refining agent accounting for 0.1-0.2% of the weight of the alloy liquid to spray and refine the aluminum-magnesium-silicon alloy liquid and the hard aluminum alloy liquid in the melting furnace for 10-20 minutes respectively to remove slag, and then scrape off the slag on the surface of the alloy liquid;
[0014] Step 3: A mixed gas consisting of argon gas with a purity of 99.99% and chlorine gas with a purity of 99.99% is introduced through the air-permeable brick installed at the bottom of the smelting furnace to refine the aluminum-magnesium-silicon alloy liquid and the hard aluminum alloy liquid for 10-20 minutes respectively for dehydrogenation treatment;
[0015] Step 4: introducing the aluminum-magnesium-silicon alloy liquid and the hard aluminum alloy liquid in the smelting furnace into the flow trough respectively, and making the alloy liquid flow through the degassing box and the tubular filter box arranged on the flow trough in turn to perform online hydrogen removal and slag removal treatment;
[0016] Step 5: Under the conditions of a casting wheel speed of 26-28 rpm and a cooling water flow rate of 9-11 liters / minute, the aluminum-magnesium-silicon alloy liquid and the hard aluminum alloy liquid at 680-690° C. are continuously cast and extruded into aluminum-magnesium-silicon alloy round rods and hard aluminum alloy round rods with a diameter of 9.5 mm respectively;
[0017] Step 6: Drawing the aluminum-magnesium-silicon alloy round rod and the hard aluminum alloy round rod into an aluminum-magnesium-silicon alloy wire with a diameter of 2-5 mm and a hard aluminum alloy wire with a diameter of 3.5-5 mm respectively;
[0018] Step 7: Aging the aluminum-magnesium-silicon alloy wire at 150-160°C for 10-12 hours, and then cooling it to room temperature with the furnace;
[0019] Step 8: Twisting the aluminum-magnesium-silicon alloy wire and the hard aluminum alloy wire to obtain the high-strength aluminum alloy core aluminum stranded wire for the overhead conductor.
[0020] Preferably, the refining agent in step 2 is composed of the following components in mass percentage: ZnCl2 44.6%, K2CO3 25.8%, NaNO3 7.9%, KF 10.5%, K2SO4 7.4%, and Li2SO4 3.8%.
[0021] Preferably, the production method of the refining agent in step 2 comprises the following steps in sequence:
[0022] (1) According to the composition and mass percentage of the refining agent, ZnCl2, K2CO3, NaNO3, KF, K2SO4, and Li2SO4 with a purity of ≥99.8% are selected as raw materials for batching;
[0023] (2) heating and melting the raw materials at 1150°C under the protection of argon gas with a purity of 99.99%, and then cooling and solidifying them into a bulk refining agent;
[0024] (3) crushing the bulk refining agent into powder with a particle size of ≤2 mm to obtain the refining agent.
[0025] Hydrogen pores and inclusions are common defects inside aluminum alloy wires. They will split the aluminum matrix in the aluminum alloy wire, hinder the movement of free electrons, and increase the scattering of free electrons, thereby causing the resistance of the aluminum alloy wire to increase and the conductivity to decrease. Hydrogen pores and inclusions will also cause local stress concentration inside the aluminum alloy wire, becoming the crack source and crack propagation direction of the aluminum alloy wire, thereby reducing the strength, plasticity and corrosion resistance of the aluminum alloy wire. Therefore, in order to solve the problem of mutual restriction between strength and conductivity and improve the strength and conductivity of the aluminum alloy wire at the same time, the purity of the aluminum alloy wire must be improved.
[0026] Traditional refining agents are mainly made of raw materials such as sodium salt, fluoride salt, chloride salt, hexachloroethane, etc., which are directly crushed and mixed. The interaction between the raw materials is not brought into play, resulting in a high melting point of the refining agent and low slag removal efficiency. In order to improve the slag removal efficiency of the alloy liquid in the furnace, the inventor has developed a high-efficiency and environmentally friendly refining agent through a large number of experimental studies. The refining agent is mainly composed of ZnCl2 and K2CO3, and a small amount of NaNO3, KF, K2SO4, and Li2SO4 are added. The raw materials are first heated and melted at 1150°C under argon protection, and then cooled, solidified and crushed into a powdery refining agent. The melting point of ZnCl2 is about 290°C, the melting point of NaNO3 is 306.8°C, the melting point of K2CO3 is 891°C, the melting point of KF is 858°C, the melting point of K2SO4 is 1069°C, and the melting point of Li2SO4 is 859 ℃, although K2CO3, KF, K2SO4, Li2SO4 have high melting points, but through melting and solidification crystallization, K2CO3 and KF form KF·K2CO3 eutectic with a melting point of only 688℃, K2SO4 and Li2SO4 form K2SO4·Li2SO4 eutectic with a melting point of only 716℃, which greatly reduces the melting point of the refining agent, and the refining agent is easier to dissolve in the alloy liquid, ZnCl2 decomposes Cl2, K2CO3 decomposes CO2, and NaNO3 decomposes N2, CO2 and NO gas. A large number of bubbles capture inclusions in the alloy liquid during the floating process, which has a slag removal effect. K2SO4·Li2SO4 eutectic melts into liquid molten salt, which has a good wetting and spheroidizing effect on inclusions such as alumina, promotes the separation of inclusions from the alloy liquid, and improves the slag removal efficiency. In addition, the refining agent does not contain sodium salt and hexachloroethane, but only contains a small amount of fluoride salt, and is more environmentally friendly to use.
[0027] Preferably, the volume percentage of chlorine in the mixed gas in step three is 3-5%, and the flow rate of the mixed gas is 1-2 cubic meters per minute.
[0028] The main function of refining the alloy liquid in the furnace by spraying a refining agent is to remove slag. Although it also has a dehydrogenation effect, the dehydrogenation effect is poor because the refining agent inevitably contains moisture, which will cause the alloy liquid to absorb hydrogen during refining. In order to reduce the hydrogen content of the alloy liquid in the furnace, the present invention installs a plurality of porous air-permeable bricks in the smelting furnace, and then passes a mixed gas composed of argon and chlorine into the alloy liquid in the furnace through the air-permeable bricks. After the mixed gas passes through the porous air-permeable bricks, it is decomposed into small and uniform small bubbles. The small bubbles capture the hydrogen in the alloy liquid during the floating process, and then float up and take out the alloy liquid, which plays a role in dehydrogenation. Since a plurality of porous air-permeable bricks are evenly installed at the bottom of the smelting furnace, the bubbles are evenly distributed in the alloy liquid, and at the same time, the bubbles have a stirring effect on the alloy liquid when floating, avoiding the dead corner of degassing in the alloy liquid in the furnace, and improving the dehydrogenation efficiency of the alloy liquid. Chlorine is added to the mixed gas, because chlorine has a stronger binding force with hydrogen atoms, thereby further improving the dehydrogenation effect. After dehydrogenation through the breathable bricks at the bottom of the furnace, the hydrogen content of the alloy liquid in the smelting furnace can be reduced to below 0.2ml / 100gAl, thereby greatly improving the purity of the alloy liquid in the furnace.
[0029] Preferably, in the step 4, the rotation speed of the graphite rotor in the degassing box is 600-700 rpm, the gas flow on the graphite rotor is 1-2 cubic meters per hour, the gas pressure is 0.8-1MPa, and the gas is a mixed gas consisting of argon with a purity of 99.99% and chlorine with a purity of 99.99%, and the volume percentage of chlorine in the mixed gas is 3-5%.
[0030] The high-speed rotating graphite rotor in the degassing box breaks the mixed gas composed of argon and chlorine into tiny bubbles and enters the alloy liquid. The hydrogen atoms in the alloy liquid are continuously diffused into the bubbles by utilizing the partial pressure difference of hydrogen between the alloy liquid and the bubbles, and then float up and escape from the alloy liquid with the bubbles, thereby removing hydrogen. After dehydrogenation in the degassing box, the hydrogen content of the alloy liquid can be reduced to below 0.08ml / 100gAl, thereby greatly improving the purity of the alloy liquid and ultimately improving the strength and conductivity of the aluminum alloy wire.
[0031] The filter medium of the tubular filter box described in step four is a ceramic filter tube, which is made of silicon nitride ceramic particles with a particle size of 3-6mm and a binder sintered at high temperature. There are a large number of tortuous pores inside. When the alloy liquid flows through the ceramic filter tube, inclusions are adsorbed or blocked on the surface of the ceramic filter tube and the inner wall of the pores, thereby achieving the effect of filtering and removing slag. The structure and use of the tubular filter box are available in public literature and will not be repeated here. Tubular filtration is a high-precision filtration. After tubular filtration, the removal rate of inclusions larger than 5μm in the alloy liquid can reach more than 98%, and the slag content of the alloy liquid can be reduced to 0.05mm 2 / kgAl or less, thereby greatly improving the purity of the aluminum alloy liquid and improving the strength and conductivity of the aluminum alloy wire.
[0032] In step 5, continuous casting and extrusion is to pour the alloy liquid into a continuous casting and extrusion machine, and then extrude the alloy round rod from the die after cooling by the casting and extrusion wheel. Continuous casting and extrusion is a highly efficient short-process forming technology, which has the advantages of small investment and small footprint compared to conventional continuous casting and rolling. The specific structure and operation method of continuous casting and extrusion are available in the literature, which will not be repeated here.
[0033] Aluminum-magnesium-silicon alloy wire is a heat-treatable strengthening alloy wire, while hard aluminum alloy wire is a non-heat-treatable strengthening alloy wire. Therefore, aluminum-magnesium-silicon alloy wire must be aged, while hard aluminum alloy wire does not need to be heat-treated. The inventors conducted a large number of experimental studies on the aging process of the aluminum-magnesium-silicon alloy wire described in the present invention and found that the aluminum-magnesium-silicon alloy wire can achieve the optimal combination of strength and conductivity by aging at 150-160°C for 10-12 hours and then cooling to room temperature with the furnace, that is, it has high strength and high conductivity. If the aging temperature is not 150-160°C or the aging time is not 10-12 hours, the optimal combination of high strength and high conductivity cannot be achieved.
[0034] The twisting and forming in step eight is to twist the aluminum-magnesium-silicon alloy wire and the hard aluminum alloy wire on a twisting machine according to the structure of the aluminum alloy core aluminum stranded wire. Since the twisting machine is a conventional mechanical equipment, there is a large amount of literature available for reference, so the structure and use of the twisting machine will not be described in detail here.
[0035] Finally, it should be pointed out that the aluminum alloy core aluminum stranded wire of the present invention must first be manufactured into two alloy wires, aluminum-magnesium-silicon alloy wire and hard aluminum alloy wire. Although the manufacturing process and technology of the two alloy wires are the same, there is a large difference in the composition of the two alloy wires, requiring the two alloy wires to be manufactured separately and independently. The two alloy wires can be manufactured separately on two production lines, or on the same production line, and finally the two alloy wires are twisted into an aluminum alloy core aluminum stranded wire.
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] (1) The present invention scientifically designs the structure of the aluminum alloy core aluminum stranded wire, adopts high-strength aluminum-magnesium-silicon alloy wire with a tensile strength greater than 340MPa to replace the basically non-conductive steel wire as the core wire of the aluminum stranded wire, and adopts high-conductivity hard aluminum alloy wire with a conductivity greater than 63% IACS to replace the ordinary hard aluminum alloy wire on the outside. Therefore, compared with the traditional steel core aluminum stranded wire, under the same cross-sectional area conditions, the aluminum alloy core aluminum stranded wire of the present invention has no hysteresis loss, lower resistance, and higher conductivity, which can reduce the power loss of the line, increase the transmission capacity of the line, and improve the transmission efficiency of the line. In addition, because aluminum is lighter and more corrosion-resistant than steel, the aluminum alloy core aluminum stranded wire of the present invention also has the advantages of light weight, large tensile force to weight ratio, good sag characteristics, long life cycle, and low maintenance cost;
[0038] (2) The present invention optimizes the manufacturing process of aluminum alloy core aluminum stranded wire, greatly improves the purity of aluminum-magnesium-silicon alloy wire and hard aluminum alloy wire, and improves the strength and conductivity of aluminum-magnesium-silicon alloy wire and hard aluminum alloy wire. Compared with ordinary aluminum alloy core aluminum stranded wire, under the same cross-sectional area, the aluminum alloy core aluminum stranded wire of the present invention has lower resistance and higher conductivity, thereby significantly reducing the power loss of the line, increasing the power transmission capacity of the line, and improving the power transmission efficiency of the line. At the same time, the manufacturing process is short, the equipment investment is small, the floor space is small, the production efficiency is high, and the production cost of the aluminum alloy core aluminum stranded wire can be greatly reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is a schematic diagram of the structure of the aluminum alloy core aluminum stranded wire described in Example 1 of the present invention.
[0040] Figure 2 This is a schematic diagram of the structure of the aluminum alloy core aluminum stranded wire described in Example 2 of the present invention.
[0041] Figure 3 This is a schematic diagram of the structure of the aluminum alloy core aluminum stranded wire described in Example 3 of the present invention. DETAILED DESCRIPTION
[0042] The technical solution of the present invention is further described below in conjunction with specific embodiments and the accompanying drawings.
[0043] Embodiment 1:
[0044] A high-strength aluminum alloy core aluminum stranded wire for overhead conductors, such as Figure 1As shown, in order from the center to the outside, a central aluminum-magnesium-silicon alloy wire 100, an aluminum-magnesium-silicon alloy wire inner layer 101, an aluminum-magnesium-silicon alloy wire middle layer 102, an aluminum-magnesium-silicon alloy wire outer layer 103, a hard aluminum alloy wire inner layer 201, a hard aluminum alloy wire middle layer 202 and a hard aluminum alloy wire outer layer 203 are arranged in sequence, the aluminum-magnesium-silicon alloy wire inner layer 101 is composed of 6 aluminum-magnesium-silicon alloy wires, the aluminum-magnesium-silicon alloy wire middle layer 102 is composed of 12 aluminum-magnesium-silicon alloy wires, the aluminum-magnesium-silicon alloy wire outer layer 103 is composed of 18 aluminum-magnesium-silicon alloy wires, the hard aluminum alloy wire inner layer 201 is composed of 19 hard aluminum alloy wires, the hard aluminum alloy wire middle layer 202 is composed of 25 hard aluminum alloy wires, the hard aluminum alloy wire outer layer 203 is composed of 32 hard aluminum alloy wires, and the aluminum-magnesium-silicon alloy wire inner layer 101 is spirally wound In the center aluminum-magnesium-silicon alloy wire 100, the aluminum-magnesium-silicon alloy wire middle layer 102 is spirally wound on the aluminum-magnesium-silicon alloy wire inner layer 101 in a direction opposite to the winding direction of the aluminum-magnesium-silicon alloy wire inner layer 101, the aluminum-magnesium-silicon alloy wire outer layer 103 is spirally wound on the aluminum-magnesium-silicon alloy wire middle layer 102 in a direction opposite to the winding direction of the aluminum-magnesium-silicon alloy wire middle layer 102, the hard aluminum alloy wire inner layer 201 is spirally wound on the aluminum-magnesium-silicon alloy wire outer layer 103 in a direction opposite to the winding direction of the aluminum-magnesium-silicon alloy wire outer layer 103, the hard aluminum alloy wire middle layer 202 is spirally wound on the hard aluminum alloy wire inner layer 201 in a direction opposite to the winding direction of the hard aluminum alloy wire inner layer 201, and the hard aluminum alloy wire outer layer 203 is spirally wound on the hard aluminum alloy wire middle layer 202 in a direction opposite to the winding direction of the hard aluminum alloy wire middle layer 202.
[0045] The diameter of the aluminum-magnesium-silicon alloy wire is 3 mm, and the aluminum-magnesium-silicon alloy wire is composed of the following components in mass percentage: Mg 1.12%, Si 0.91%, and the balance is Al and unavoidable impurities, with a single impurity ≤0.05% and a total impurity ≤0.1%.
[0046] The diameter of the hard aluminum alloy wire is 4 mm, and the hard aluminum alloy wire is composed of the following components in mass percentage: Fe0.26%, and the balance is Al and inevitable impurities, with a single impurity ≤0.05% and a total impurity amount ≤0.1%.
[0047] The manufacturing method of high-strength aluminum alloy core aluminum stranded wire for overhead conductors comprises the following steps in sequence:
[0048] Step 1: melting and preparing aluminum-magnesium-silicon alloy liquid and hard aluminum alloy liquid at 710° C. according to the components and mass percentages of the aluminum-magnesium-silicon alloy wire and the hard aluminum alloy wire;
[0049] Step 2: Use argon gas with a purity of 99.99% and a refining agent accounting for 0.15% of the weight of the alloy liquid to spray and refine the aluminum-magnesium-silicon alloy liquid and the hard aluminum alloy liquid in the melting furnace for 15 minutes respectively to remove slag, and then scrape off the slag on the surface of the alloy liquid;
[0050] Step 3: A mixed gas consisting of argon with a purity of 99.99% and chlorine with a purity of 99.99% is introduced through the air-permeable brick installed at the bottom of the smelting furnace to refine the aluminum-magnesium-silicon alloy liquid and the hard aluminum alloy liquid for 15 minutes respectively for dehydrogenation treatment, the volume percentage of chlorine in the mixed gas is 4%, and the flow rate of the mixed gas is 1.5 cubic meters / minute;
[0051] Step 4: introducing the aluminum-magnesium-silicon alloy liquid and the hard aluminum alloy liquid in the smelting furnace into the flow trough respectively, and making the alloy liquid flow through the degassing box and the tubular filter box arranged on the flow trough in turn for online dehydrogenation and slag removal treatment, the rotation speed of the graphite rotor in the degassing box is 650 rpm, the gas flow rate on the graphite rotor is 1.5 cubic meters / hour, and the gas pressure is 0.9MPa. The gas is a mixed gas composed of argon with a purity of 99.99% and chlorine with a purity of 99.99%, and the volume percentage of chlorine in the mixed gas is 4%;
[0052] Step 5: Under the conditions of a casting wheel speed of 27 rpm and a cooling water flow rate of 10 liters / minute, the 685° C. aluminum-magnesium-silicon alloy liquid and the hard aluminum alloy liquid are continuously cast and extruded into aluminum-magnesium-silicon alloy round rods and hard aluminum alloy round rods with a diameter of 9.5 mm respectively;
[0053] Step 6: Drawing the aluminum-magnesium-silicon alloy round rod and the hard aluminum alloy round rod into an aluminum-magnesium-silicon alloy wire with a diameter of 3 mm and a hard aluminum alloy wire with a diameter of 4 mm respectively;
[0054] Step 7: Aging the aluminum-magnesium-silicon alloy wire at 155°C for 11 hours, and then cooling it to room temperature with the furnace;
[0055] Step 8: Twisting the aluminum-magnesium-silicon alloy wire and the hard aluminum alloy wire to obtain the high-strength aluminum alloy core aluminum stranded wire for the overhead conductor.
[0056] Embodiment 2:
[0057] A high-strength aluminum alloy core aluminum stranded wire for overhead conductors, such as Figure 2As shown, in order from the center to the outside, a central aluminum-magnesium-silicon alloy wire 100, an aluminum-magnesium-silicon alloy wire inner layer 101, an aluminum-magnesium-silicon alloy wire middle layer 102, an aluminum-magnesium-silicon alloy wire outer layer 103, a hard aluminum alloy wire inner layer 201, a hard aluminum alloy wire middle layer 202 and a hard aluminum alloy wire outer layer 203 are sequentially arranged, the aluminum-magnesium-silicon alloy wire inner layer 101 is composed of 6 aluminum-magnesium-silicon alloy wires, the aluminum-magnesium-silicon alloy wire middle layer 102 is composed of 12 aluminum-magnesium-silicon alloy wires, the aluminum-magnesium-silicon alloy wire outer layer 103 is composed of 18 aluminum-magnesium-silicon alloy wires, the hard aluminum alloy wire inner layer 201 is composed of 11 hard aluminum alloy wires, the hard aluminum alloy wire middle layer 202 is composed of 18 hard aluminum alloy wires, the hard aluminum alloy wire outer layer 203 is composed of 24 hard aluminum alloy wires, and the aluminum-magnesium-silicon alloy wire inner layer 101 is spirally wound In the center aluminum-magnesium-silicon alloy wire 100, the aluminum-magnesium-silicon alloy wire middle layer 102 is spirally wound on the aluminum-magnesium-silicon alloy wire inner layer 101 in a direction opposite to the winding direction of the aluminum-magnesium-silicon alloy wire inner layer 101, the aluminum-magnesium-silicon alloy wire outer layer 103 is spirally wound on the aluminum-magnesium-silicon alloy wire middle layer 102 in a direction opposite to the winding direction of the aluminum-magnesium-silicon alloy wire middle layer 102, the hard aluminum alloy wire inner layer 201 is spirally wound on the aluminum-magnesium-silicon alloy wire outer layer 103 in a direction opposite to the winding direction of the aluminum-magnesium-silicon alloy wire outer layer 103, the hard aluminum alloy wire middle layer 202 is spirally wound on the hard aluminum alloy wire inner layer 201 in a direction opposite to the winding direction of the hard aluminum alloy wire inner layer 201, and the hard aluminum alloy wire outer layer 203 is spirally wound on the hard aluminum alloy wire middle layer 202 in a direction opposite to the winding direction of the hard aluminum alloy wire middle layer 202.
[0058] The diameter of the aluminum-magnesium-silicon alloy wire is 2 mm, and the aluminum-magnesium-silicon alloy wire is composed of the following components in mass percentage: Mg 1.15%, Si 0.88%, and the balance is Al and unavoidable impurities, with a single impurity ≤0.05% and a total impurity ≤0.1%.
[0059] The diameter of the hard aluminum alloy wire is 5 mm, and the hard aluminum alloy wire is composed of the following components in mass percentage: Fe0.23%, and the balance is Al and inevitable impurities, with a single impurity ≤0.05% and a total impurity amount ≤0.1%.
[0060] The manufacturing method of high-strength aluminum alloy core aluminum stranded wire for overhead conductors comprises the following steps in sequence:
[0061] Step 1: melting and preparing aluminum-magnesium-silicon alloy liquid and hard aluminum alloy liquid at 700° C. according to the components and mass percentages of the aluminum-magnesium-silicon alloy wire and the hard aluminum alloy wire;
[0062] Step 2: Use argon gas with a purity of 99.99% and a refining agent accounting for 0.2% of the weight of the alloy liquid to spray and refine the aluminum-magnesium-silicon alloy liquid and the hard aluminum alloy liquid in the melting furnace for 20 minutes to remove slag, and then scrape off the slag on the surface of the alloy liquid;
[0063] Step 3: A mixed gas consisting of argon with a purity of 99.99% and chlorine with a purity of 99.99% is introduced through the air-permeable brick installed at the bottom of the smelting furnace to refine the aluminum-magnesium-silicon alloy liquid and the hard aluminum alloy liquid for 10 minutes respectively for dehydrogenation treatment, the volume percentage of chlorine in the mixed gas is 5%, and the flow rate of the mixed gas is 2 cubic meters / minute;
[0064] Step 4: introducing the aluminum-magnesium-silicon alloy liquid and the hard aluminum alloy liquid in the smelting furnace into the flow trough respectively, and making the alloy liquid flow through the degassing box and the tubular filter box arranged on the flow trough in turn for online dehydrogenation and slag removal treatment, the rotation speed of the graphite rotor in the degassing box is 600 rpm, the gas flow rate on the graphite rotor is 2 cubic meters / hour, the gas pressure is 1MPa, and the gas is a mixed gas composed of argon with a purity of 99.99% and chlorine with a purity of 99.99%, and the volume percentage of chlorine in the mixed gas is 5%;
[0065] Step 5: Under the conditions of a casting wheel speed of 28 rpm and a cooling water flow rate of 9 liters / minute, the 680° C. aluminum-magnesium-silicon alloy liquid and the hard aluminum alloy liquid are continuously cast and extruded into aluminum-magnesium-silicon alloy round rods and hard aluminum alloy round rods with a diameter of 9.5 mm respectively;
[0066] Step 6: Drawing the aluminum-magnesium-silicon alloy round rod and the hard aluminum alloy round rod into an aluminum-magnesium-silicon alloy wire with a diameter of 2 mm and a hard aluminum alloy wire with a diameter of 5 mm respectively;
[0067] Step 7: ageing the aluminum-magnesium-silicon alloy wire at 150°C for 12 hours, and then cooling it to room temperature along with the furnace;
[0068] Step 8: Twisting the aluminum-magnesium-silicon alloy wire and the hard aluminum alloy wire to obtain the high-strength aluminum alloy core aluminum stranded wire for the overhead conductor.
[0069] Embodiment 3:
[0070] A high-strength aluminum alloy core aluminum stranded wire for overhead conductors, such as Figure 3As shown, in order from the center to the outside, a central aluminum-magnesium-silicon alloy wire 100, an aluminum-magnesium-silicon alloy wire inner layer 101, an aluminum-magnesium-silicon alloy wire middle layer 102, an aluminum-magnesium-silicon alloy wire outer layer 103, a hard aluminum alloy wire inner layer 201, a hard aluminum alloy wire middle layer 202 and a hard aluminum alloy wire outer layer 203 are arranged in sequence, the aluminum-magnesium-silicon alloy wire inner layer 101 is composed of 6 aluminum-magnesium-silicon alloy wires, the aluminum-magnesium-silicon alloy wire middle layer 102 is composed of 12 aluminum-magnesium-silicon alloy wires, the aluminum-magnesium-silicon alloy wire outer layer 103 is composed of 18 aluminum-magnesium-silicon alloy wires, the hard aluminum alloy wire inner layer 201 is composed of 24 hard aluminum alloy wires, the hard aluminum alloy wire middle layer 202 is composed of 30 hard aluminum alloy wires, the hard aluminum alloy wire outer layer 203 is composed of 36 hard aluminum alloy wires, and the aluminum-magnesium-silicon alloy wire inner layer 101 is spirally wound In the center aluminum-magnesium-silicon alloy wire 100, the aluminum-magnesium-silicon alloy wire middle layer 102 is spirally wound on the aluminum-magnesium-silicon alloy wire inner layer 101 in a direction opposite to the winding direction of the aluminum-magnesium-silicon alloy wire inner layer 101, the aluminum-magnesium-silicon alloy wire outer layer 103 is spirally wound on the aluminum-magnesium-silicon alloy wire middle layer 102 in a direction opposite to the winding direction of the aluminum-magnesium-silicon alloy wire middle layer 102, the hard aluminum alloy wire inner layer 201 is spirally wound on the aluminum-magnesium-silicon alloy wire outer layer 103 in a direction opposite to the winding direction of the aluminum-magnesium-silicon alloy wire outer layer 103, the hard aluminum alloy wire middle layer 202 is spirally wound on the hard aluminum alloy wire inner layer 201 in a direction opposite to the winding direction of the hard aluminum alloy wire inner layer 201, and the hard aluminum alloy wire outer layer 203 is spirally wound on the hard aluminum alloy wire middle layer 202 in a direction opposite to the winding direction of the hard aluminum alloy wire middle layer 202.
[0071] The diameter of the aluminum-magnesium-silicon alloy wire is 3.5 mm, and the aluminum-magnesium-silicon alloy wire is composed of the following components in mass percentage: Mg 1.1%, Si 0.92%, and the balance is Al and unavoidable impurities, with a single impurity ≤0.05% and a total impurity ≤0.1%.
[0072] The diameter of the hard aluminum alloy wire is 3.5 mm, and the hard aluminum alloy wire is composed of the following components in mass percentage: Fe0.27%, and the balance is Al and inevitable impurities, with a single impurity ≤0.05% and a total impurity amount ≤0.1%.
[0073] The manufacturing method of high-strength aluminum alloy core aluminum stranded wire for overhead conductors comprises the following steps in sequence:
[0074] Step 1: melting and preparing aluminum-magnesium-silicon alloy liquid and hard aluminum alloy liquid at 720° C. according to the components and mass percentages of the aluminum-magnesium-silicon alloy wire and the hard aluminum alloy wire;
[0075] Step 2: Use argon gas with a purity of 99.99% and a refining agent accounting for 0.1% of the weight of the alloy liquid to spray and refine the aluminum-magnesium-silicon alloy liquid and the hard aluminum alloy liquid in the melting furnace for 10 minutes respectively to remove slag, and then scrape off the slag on the surface of the alloy liquid;
[0076] Step 3: A mixed gas consisting of argon with a purity of 99.99% and chlorine with a purity of 99.99% is introduced through the air-permeable brick installed at the bottom of the smelting furnace to refine the aluminum-magnesium-silicon alloy liquid and the hard aluminum alloy liquid for 20 minutes respectively for dehydrogenation treatment, the volume percentage of chlorine in the mixed gas is 3%, and the flow rate of the mixed gas is 1 cubic meter / minute;
[0077] Step 4: introducing the aluminum-magnesium-silicon alloy liquid and the hard aluminum alloy liquid in the smelting furnace into the flow trough respectively, and making the alloy liquid flow through the degassing box and the tubular filter box arranged on the flow trough in turn for online dehydrogenation and slag removal treatment, the rotation speed of the graphite rotor in the degassing box is 700 rpm, the gas flow rate on the graphite rotor is 1 cubic meter / hour, the gas pressure is 0.8MPa, and the gas is a mixed gas composed of argon with a purity of 99.99% and chlorine with a purity of 99.99%, and the volume percentage of chlorine in the mixed gas is 3%;
[0078] Step 5: Under the conditions of a casting wheel speed of 28 rpm and a cooling water flow rate of 11 liters / minute, the 690° C. aluminum-magnesium-silicon alloy liquid and the hard aluminum alloy liquid are continuously cast and extruded into aluminum-magnesium-silicon alloy round rods and hard aluminum alloy round rods with a diameter of 9.5 mm respectively;
[0079] Step 6: Drawing the aluminum-magnesium-silicon alloy round rod and the hard aluminum alloy round rod into an aluminum-magnesium-silicon alloy wire and a hard aluminum alloy wire with a diameter of 3.5 mm respectively;
[0080] Step 7: Aging the aluminum-magnesium-silicon alloy wire at 160°C for 10 hours, and then cooling it to room temperature along with the furnace;
[0081] Step 8: Twisting the aluminum-magnesium-silicon alloy wire and the hard aluminum alloy wire to obtain the high-strength aluminum alloy core aluminum stranded wire for the overhead conductor.
[0082] In Examples 1-3, the refining agent in step 2 is composed of the following components in mass percentage: ZnCl2 44.6%, K2CO3 25.8%, NaNO3 7.9%, KF 10.5%, K2SO4 7.4%, and Li2SO4 3.8%. The production method of the refining agent comprises the following steps in sequence: (1) selecting ZnCl2, K2CO3, NaNO3, KF, K2SO4, and Li2SO4 with a purity ≥99.8% as raw materials for batching according to the composition and mass percentage of the refining agent; (2) heating the raw materials to melt at 1150°C under the protection of argon gas with a purity of 99.99%, and then cooling and solidifying them into a bulk refining agent; (3) crushing the bulk refining agent into powder with a particle size ≤2 mm to obtain the refining agent.
[0083] Comparative Example 1:
[0084] The structure of the aluminum alloy core aluminum stranded wire, the composition of the aluminum-magnesium-silicon alloy wire and the hard aluminum alloy wire, and the manufacturing method are the same as those in Example 1, except that the refining agent used in step 2 is a currently commonly used commercially available refining agent, and the refining agent is composed of the following components in mass percentage: 26.1% NaCl, 10.6% Na2SiF6, 17.1% Na2SO4, 6.9% CaF2, 9.3% C6Cl6, 14.3% Na2S2O3 and 15.7% NaF. The production method of the refining agent is to directly crush the raw materials into powder with a particle size of ≤2 mm and then mix them.
[0085] Comparative Example 2:
[0086] The structure of the aluminum alloy core aluminum stranded wire, the composition of the aluminum-magnesium-silicon alloy wire and the hard aluminum alloy wire, and the manufacturing method are the same as those in Example 2, except that in step three, a mixed gas consisting of argon and chlorine is not introduced into the aluminum alloy liquid in the furnace through the furnace bottom air bricks for dehydrogenation treatment.
[0087] Comparative Example 3:
[0088] The structure of the aluminum alloy core aluminum stranded wire, the composition of the aluminum-magnesium-silicon alloy wire and the hard aluminum alloy wire, and the manufacturing method are the same as those in Example 3, except that in step 4, no tubular filter box is used to filter the alloy liquid.
[0089] Verification Example 1:
[0090] The melting points of the refining agents used in Example 1 and Comparative Example 1 were respectively detected by using an OXFORD-DSC500 differential scanning calorimeter, and the results are shown in Table 1. As can be seen from Table 1, the melting start temperature of the refining agent in Example 1 is 290°C, and the melting end temperature is only 716°C. The melting start temperature of the refining agent in Comparative Example 1 is 564°C, and the melting end temperature is 1249°C. By comparison, it can be seen that the refining agent developed by the present invention has a lower melting start temperature and melting end temperature, indicating that the refining agent developed by the present invention is more easily dissolved in the alloy liquid, which is beneficial to improving the slag removal effect.
[0091] Table 1 Melting point of refining agent in Example 1 and Comparative Example 1
[0092] Example 1 Comparative Example 1 Melting start temperature / ℃ 290 564 Melting end temperature / ℃ 716 1249
[0093] Verification Example 2:
[0094] The hydrogen content and slag content of the alloy liquids before casting and extrusion of Examples 1-3 and Comparative Examples 1-3 were tested on site using a HDA-V hydrogen meter and an Analyze PoDFA slag meter. The results are shown in Table 2. As can be seen from Table 2, the hydrogen content of the alloy liquids of Examples 1-3 is less than 0.08 ml / 100 gAl, and the slag content is less than 0.05 mm 2 / kgAl. However, since Comparative Example 1 uses a traditional commercial refining agent for in-furnace spray refining, Comparative Example 2 does not use a ventilation brick at the bottom of the furnace for refining, and Comparative Example 3 does not use a tubular filter box for filtration, the gas-slag content of the alloy liquid is significantly higher than that of the alloy liquid in the embodiment. By comparison, it can be seen that the present invention can greatly improve the purity of aluminum-magnesium-silicon alloy wire and hard aluminum alloy wire.
[0095] Table 2 Hydrogen content and slag content of alloy liquid before casting
[0096] Hydrogen content / (ml / 100gAl) <![CDATA[Sludge content / (mm 2 / kg) <!-- 8 -->]]> Example 1 0.074 0.045 Example 2 0.068 0.048 Example 3 0.072 0.039 Comparative Example 1 0.086 0.079 Comparative Example 2 0.131 0.053 Comparative Example 3 0.079 0.113
[0097] Verification Example 3:
[0098] Samples were taken from the aluminum-magnesium-silicon alloy wire and the hard aluminum alloy wire of Examples 1-3 and Comparative Examples 1-3, and then the room temperature tensile mechanical properties, DC resistivity and conductivity at 20°C of the aluminum-magnesium-silicon alloy wire and the hard aluminum alloy wire were tested respectively. The results are shown in Tables 3 and 4. As can be seen from Tables 3 and 4, the tensile strength of the aluminum-magnesium-silicon alloy wire of Examples 1-3 is ≥340.4MPa, the yield strength is ≥320.9MPa, the elongation after fracture is ≥5.4%, and the DC resistivity at 20°C is ≤0.0307Ω·mm 2 / m, electrical conductivity ≥56.1%IACS. The tensile strength of hard aluminum alloy wire is ≥200.9MPa, the yield strength is ≥181.5MPa, the elongation after fracture is ≥8.1%, and the DC resistivity at 20℃ is ≤0.0272Ω·mm 2 / m, conductivity ≥ 63.5% IACS. Comparative Example 1 uses a traditional commercial refining agent for furnace spray refining, Comparative Example 2 does not use the ventilation bricks at the bottom of the furnace for ventilation refining, and Comparative Example 3 does not use a tubular filter box for filtration, resulting in the strength and conductivity of the aluminum-magnesium-silicon alloy wire and the hard aluminum alloy wire being significantly lower than the strength and conductivity of the aluminum-magnesium-silicon alloy wire and the hard aluminum alloy wire in the embodiment. By comparison, it can be seen that the present invention can greatly improve the strength and conductivity of the alloy wire by improving the purity of the alloy wire.
[0099] Table 3 Room temperature tensile mechanical properties, DC resistivity and conductivity of Al-Mg-Si alloy wire at 20°C
[0100]
[0101] Table 4 Room temperature tensile mechanical properties, DC resistivity and conductivity of hard aluminum alloy wire at 20℃
[0102]
[0103] The present invention is described by way of embodiments, but does not constitute a limitation to the present invention. With reference to the description of the present invention, other changes to the disclosed embodiments are easily conceivable to professionals in the field, and such changes should fall within the scope defined by the claims of the present invention.
Claims
1. A high-strength aluminum alloy core aluminum stranded wire for overhead conductors, characterized in that: A central aluminum-magnesium-silicon alloy wire, an aluminum-magnesium-silicon alloy wire inner layer, an aluminum-magnesium-silicon alloy wire middle layer, an aluminum-magnesium-silicon alloy wire outer layer, a hard aluminum alloy wire inner layer, a hard aluminum alloy wire middle layer and a hard aluminum alloy wire outer layer are sequentially arranged from the center to the outside, wherein the aluminum-magnesium-silicon alloy wire inner layer, the aluminum-magnesium-silicon alloy wire middle layer and the aluminum-magnesium-silicon alloy wire outer layer are respectively composed of a plurality of aluminum-magnesium-silicon alloy wires, the hard aluminum alloy wire inner layer, the hard aluminum alloy wire middle layer and the hard aluminum alloy wire outer layer are respectively composed of a plurality of hard aluminum alloy wires, the aluminum-magnesium-silicon alloy wire inner layer is spirally wound around the central aluminum-magnesium-silicon alloy wire, and the aluminum-magnesium-silicon alloy wire middle layer is wound in a direction opposite to that of the aluminum-magnesium-silicon alloy wire inner layer The inner layer of the aluminum-magnesium-silicon alloy wire is spirally wound in the direction of the inner layer of the aluminum-magnesium-silicon alloy wire, the outer layer of the aluminum-magnesium-silicon alloy wire is spirally wound in the direction opposite to the winding direction of the middle layer of the aluminum-magnesium-silicon alloy wire, the inner layer of the hard aluminum alloy wire is spirally wound in the direction opposite to the winding direction of the outer layer of the aluminum-magnesium-silicon alloy wire, the middle layer of the hard aluminum alloy wire is spirally wound in the direction opposite to the winding direction of the inner layer of the hard aluminum alloy wire, and the outer layer of the hard aluminum alloy wire is spirally wound in the direction opposite to the winding direction of the middle layer of the hard aluminum alloy wire; the manufacturing method of high-strength aluminum alloy core aluminum stranded wire comprises the following steps in sequence: Step 1: melting and preparing aluminum-magnesium-silicon alloy liquid and hard aluminum alloy liquid at 700-720° C. according to the components and mass percentage of aluminum-magnesium-silicon alloy wire and hard aluminum alloy wire; Step 2: Use argon gas with a purity of 99.99% and a refining agent accounting for 0.1-0.2% of the weight of the alloy liquid to spray and refine the aluminum-magnesium-silicon alloy liquid and the hard aluminum alloy liquid in the melting furnace for 10-20 minutes respectively to remove slag, and then scrape off the slag on the surface of the alloy liquid; Step 3: A mixed gas consisting of argon gas with a purity of 99.99% and chlorine gas with a purity of 99.99% is introduced through the air-permeable brick installed at the bottom of the smelting furnace to refine the aluminum-magnesium-silicon alloy liquid and the hard aluminum alloy liquid for 10-20 minutes respectively for dehydrogenation treatment; Step 4: introducing the aluminum-magnesium-silicon alloy liquid and the hard aluminum alloy liquid in the smelting furnace into the flow trough respectively, and making the alloy liquid flow through the degassing box and the tubular filter box arranged on the flow trough in turn to perform online hydrogen removal and slag removal treatment; Step 5: Under the conditions of a casting wheel speed of 26-28 rpm and a cooling water flow rate of 9-11 liters / minute, the aluminum-magnesium-silicon alloy liquid and the hard aluminum alloy liquid at 680-690° C. are continuously cast and extruded into aluminum-magnesium-silicon alloy round rods and hard aluminum alloy round rods with a diameter of 9.5 mm respectively; Step 6: Drawing the aluminum-magnesium-silicon alloy round rod and the hard aluminum alloy round rod into an aluminum-magnesium-silicon alloy wire with a diameter of 2-3.5 mm and a hard aluminum alloy wire with a diameter of 3.5-5 mm respectively; Step 7: Aging the aluminum-magnesium-silicon alloy wire at 150-160°C for 10-12 hours, and then cooling it to room temperature with the furnace; Step 8: twisting the aluminum-magnesium-silicon alloy wire and the hard aluminum alloy wire to obtain the high-strength aluminum alloy core aluminum stranded wire for the overhead conductor; The refining agent in step 2 is composed of the following components in mass percentage: ZnCl2 44.6%, K2CO3 25.8%, NaNO37.9%, KF 10.5%, K2SO4 7.4%, and Li2SO4 3.8%.
2. The high-strength aluminum alloy core aluminum stranded wire for overhead conductors according to claim 1, characterized in that: The diameter of the aluminum-magnesium-silicon alloy wire is 2-3.5 mm, the tensile strength of the aluminum-magnesium-silicon alloy wire is ≥340.4 MPa, the yield strength is ≥320.9 MPa, the elongation after fracture is ≥5.4%, and the DC resistivity at 20°C is ≤0.0307 Ω•mm 2 / m, electrical conductivity ≥56.1%IACS.
3. The high-strength aluminum alloy core aluminum stranded wire for overhead conductors according to claim 1, characterized in that: The diameter of the hard aluminum alloy wire is 3.5-5 mm, the tensile strength of the hard aluminum alloy wire is ≥200.9 MPa, the yield strength is ≥181.5 MPa, the elongation after fracture is ≥8.1%, and the DC resistivity at 20°C is ≤0.0272 Ω•mm 2 / m, electrical conductivity ≥63.5%IACS.
4. The high-strength aluminum alloy core aluminum stranded wire for overhead conductors according to claim 1, characterized in that: The aluminum-magnesium-silicon alloy wire is composed of the following components in mass percentage: Mg 1.1-1.15%, Si 0.88-0.92%, and the balance is Al and unavoidable impurities, with a single impurity ≤0.05% and a total impurity content ≤0.1%.
5. The high-strength aluminum alloy core aluminum stranded wire for overhead conductor according to claim 1, characterized in that: The hard aluminum alloy wire is composed of the following components in mass percentage: Fe 0.23-0.27%, the balance being Al and inevitable impurities, with a single impurity ≤0.05% and a total impurity content ≤0.1%.
6. A method for manufacturing a high-strength aluminum alloy core aluminum stranded wire for overhead conductors, the method being used to manufacture the aluminum alloy core aluminum stranded wire according to any one of claims 1 to 5, characterized in that: The following steps are included in sequence: Step 1: melting and preparing aluminum-magnesium-silicon alloy liquid and hard aluminum alloy liquid at 700-720° C. according to the components and mass percentage of aluminum-magnesium-silicon alloy wire and hard aluminum alloy wire; Step 2: Use argon gas with a purity of 99.99% and a refining agent accounting for 0.1-0.2% of the weight of the alloy liquid to spray and refine the aluminum-magnesium-silicon alloy liquid and the hard aluminum alloy liquid in the melting furnace for 10-20 minutes respectively to remove slag, and then scrape off the slag on the surface of the alloy liquid; Step 3: A mixed gas consisting of argon gas with a purity of 99.99% and chlorine gas with a purity of 99.99% is introduced through the air-permeable brick installed at the bottom of the smelting furnace to refine the aluminum-magnesium-silicon alloy liquid and the hard aluminum alloy liquid for 10-20 minutes respectively for dehydrogenation treatment; Step 4: introducing the aluminum-magnesium-silicon alloy liquid and the hard aluminum alloy liquid in the smelting furnace into the flow trough respectively, and making the alloy liquid flow through the degassing box and the tubular filter box arranged on the flow trough in turn to perform online hydrogen removal and slag removal treatment; Step 5: Under the conditions of a casting wheel speed of 26-28 rpm and a cooling water flow rate of 9-11 liters / minute, the aluminum-magnesium-silicon alloy liquid and the hard aluminum alloy liquid at 680-690° C. are continuously cast and extruded into aluminum-magnesium-silicon alloy round rods and hard aluminum alloy round rods with a diameter of 9.5 mm respectively; Step 6: Drawing the aluminum-magnesium-silicon alloy round rod and the hard aluminum alloy round rod into an aluminum-magnesium-silicon alloy wire with a diameter of 2-3.5 mm and a hard aluminum alloy wire with a diameter of 3.5-5 mm respectively; Step 7: Aging the aluminum-magnesium-silicon alloy wire at 150-160°C for 10-12 hours, and then cooling it to room temperature with the furnace; Step 8: twisting the aluminum-magnesium-silicon alloy wire and the hard aluminum alloy wire to obtain the high-strength aluminum alloy core aluminum stranded wire for the overhead conductor; The refining agent in step 2 is composed of the following components in mass percentage: ZnCl2 44.6%, K2CO3 25.8%, NaNO37.9%, KF 10.5%, K2SO4 7.4%, and Li2SO4 3.8%.
7. The method for manufacturing a high-strength aluminum alloy core aluminum stranded wire for overhead conductors according to claim 6, characterized in that: The production method of the refining agent in step 2 comprises the following steps in sequence: (1) According to the composition and mass percentage of the refining agent, ZnCl2, K2CO3, NaNO3, KF, K2SO4 and Li2SO4 with a purity of ≥99.8% are selected as raw materials for batching; (2) The raw materials are heated and melted at 1150°C under the protection of argon gas with a purity of 99.99%, and then cooled and solidified into a bulk refining agent; (3) Crushing the bulk refining agent into powder with a particle size of ≤2 mm to obtain the refining agent.
8. The method for manufacturing a high-strength aluminum alloy core aluminum stranded wire for overhead conductors according to claim 6, characterized in that: In the step 3, the volume percentage of chlorine in the mixed gas is 3-5%, and the flow rate of the mixed gas is 1-2 cubic meters per minute.
9. The method for manufacturing a high-strength aluminum alloy core aluminum stranded wire for overhead conductors according to claim 6, characterized in that: In the step 4, the rotation speed of the graphite rotor in the degassing box is 600-700 rpm, the gas flow on the graphite rotor is 1-2 cubic meters per hour, the gas pressure is 0.8-1 MPa, and the gas is a mixed gas consisting of argon with a purity of 99.99% and chlorine with a purity of 99.99%, and the volume percentage of chlorine in the mixed gas is 3-5%.
Citation Information
Patent Citations
Aluminum alloy core aluminum stranded conductor
CN204792029U
Special high strength steel core aluminium alloy stranded conductor
CN205428511U